Benefit of Flow-Controlled Over Pressure-Regulated Volume Control Mode During One-Lung Ventilation: A Randomized Experimental Crossover Study. (20th December 2022) - Schranc, Álmos; Diaper, John; Südy, Roberta; Fodor, Gergely H.; Habre, Walid; Albu, Gergely
Abstract : BACKGROUND: Application of a ventilation modality that ensures adequate gas exchange during one-lung ventilation (OLV) without inducing lung injury is of paramount importance. Due to its beneficial effects on respiratory mechanics and gas exchange, flow-controlled ventilation (FCV) may be considered as a protective alternative mode of traditional pressure- or volume-controlled ventilation during OLV. We investigated whether this new modality provides benefits compared with conventional ventilation modality for OLV. METHODS: Ten pigs were anaesthetized and randomly assigned in a crossover design to be ventilated with FCV or pressure-regulated volume control (PRVC) ventilation. Arterial partial pressure of oxygen (Pao 2 ), carbon dioxide (Paco 2 ), ventilation and hemodynamical parameters, and lung aeration measured by electrical impedance tomography were assessed at baseline and 1 hour after the application of each modality during OLV using an endobronchial blocker. RESULTS: Compared to PRVC, FCV resulted in increased Pao 2 (153.7 ± 12.7 vs 169.9 ± 15.0 mm Hg; P = .002) and decreased Paco 2 (53.0 ± 11.0 vs 43.2 ± 6.0 mm Hg; P < .001) during OLV, with lower respiratory elastance (103.7 ± 9.5 vs 77.2 ± 10.5 cm H2 O/L; P < .001) and peak inspiratory pressure values (27.4 ± 1.9 vs 22.0 ± 2.3 cm H2 O; P < .001). No differences in lung aeration or hemodynamics could be detected between the 2 ventilation modalities. CONCLUSIONS: The application of FCV in OLV led to improvement in gas exchange and respiratory elastance with lower ventilatory pressures. Our findings suggest that FCV may offer an optimal, protective ventilation modality for OLV.